2017
DOI: 10.14202/vetworld.2017.221-226
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of antibacterial and antioxidant activity of Cassia tora extract toward its growth promoting effect in broiler birds

Abstract: Aim:The study was conducted to evaluate the attribution of antibacterial and antioxidant activity of methanolic extract of Cassia tora toward its growth promoting effect in broiler birds.Materials and Methods:A limit test was conducted for C. tora extract in Wistar albino rats. Phytochemical screening of methanolic extract of leaves of C. tora was carried out. In-vitro antibacterial activity was measured by disc diffusion method. 1-day-old Ven Cobb broiler birds (n=90) were randomly allocated into three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…The introduction of the probiotic preparation into the diet influences activation of β-lysine in blood serum; this indicator increases by 16.1% (p≤0.05), compared to the reference group. This fact is consistent with the results of previous studies [ 45 ].…”
Section: Resultssupporting
confidence: 94%
“…The introduction of the probiotic preparation into the diet influences activation of β-lysine in blood serum; this indicator increases by 16.1% (p≤0.05), compared to the reference group. This fact is consistent with the results of previous studies [ 45 ].…”
Section: Resultssupporting
confidence: 94%
“…Similarly, Asba and Meeta (2017) studied various phytoconstituents in roots, leaves, stem, flowers and pods of C. tora in different solvents (six solvents) and most of the phytochemicals were reported from the aqueous and methanol extract as compared to other solvent extracts. Suradkar et al (2017) and Sahu et al (2017) reported the presence of alkaloids, flavonoids, saponins, tannins, phenols, steroids etc. in ethanol, aqueous and methanol extracts of the leaves.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…[68] Seed extract Cassia surattensis shows antioxidant activity against paracetamol intoxication in mice: In vitro and in vivo Studies of Herbal Green. [69] The importance of C. fistula in diseases control has ancient background due to high sources of antioxidants. Mainly green floral parts of plants which are used as green tea showed strong antioxidant potential are due to the presence of tocopherol, flavonoids, and polyphenols, [70,71] Intake of bioflavonoids provides freshness due to ferric ion reducing capacity.…”
Section: Antioxidant Activitymentioning
confidence: 99%